[66] Right transperitoneal laparoscopic ureterolithotomy - Amine Saouli (Taylor & Francis Group, 2018)
Objective: To report our experience of laparoscopic ureterolithotomy and its effectiveness, as this technique is an excellent alternative to ureteroscopy in the treatment of large ureteric stones. Methods: We present a laparoscopic right lumbar ureterolithotomy in a 55-year-old patient with obstructive pyelonephritis on two lumbar calculi measuring 18 and 20 mm, respectively. Results: Urinary drainage was ensured by percutaneous nephrostomy, which was placed preoperatively and removed 15 days postoperatively; there were no postoperative complications, and a fast learning curve. Excellent results were obtained, with no residual fragments. Conclusion: Laparoscopic ureterolithotomy is an effective and reliable surgical procedure with better results (without residual fragments) compared to ureteroscopy.